Efficacy of split hours part-time patching versus continuous hours part-time patching for treatment of anisometropic amblyopia in children: a pilot study. Issue 7 (15th May 2013) - Sachdeva, Virender; Mittal, Vaibhev; Kekunnaya, Ramesh; Gupta, Amit; Rao, Harsha L; Mollah, Joseph; Sontha, Anand; Gunturu, Rekha; Rao, B Venkateshwar
Abstract : Aim: To compare efficacy of 'split hours part-time patching' and 'continuous hours part-time patching' for the treatment of anisometropic amblyopia. Methods: We designed a prospective, interventional, non-randomised, comparative pilot study involving children between 4 and 11 years of age with anisometropic amblyopia who were treated with either continuous wear (Group A) or split hours part-time patching (Group B) as per parents wish, after appropriate discussion with the parents. Children were followed-up for the improvement in visual acuity and the compliance at each follow-up visit. Results: 44 and 24 children were recruited in Group A and Group B, respectively (mean±SD baseline BCVA of the amblyopic eye: 0.99±0.32 and 0.95±0.23 logMAR, respectively). BCVA (adjusted for baseline BCVA and age) at 3 months in Group A (0.59±0.24) was comparable (p=0.08) with that in Group B (0.71±0.24). This was same even at 6 months (0.51±0.25 in Group A and 0.59±0.25 in Group B, p=0.25). The improvement in BCVA at 3 months was also comparable (p=0.06) in Group A (0.39±0.23) and Group B (0.26±0.23). The improvement in BCVA at 6 months was also comparable (p=0.14) in Group A (0.47±0.26) and Group B (0.37±0.26). Conclusions: Both patching regimens lead to significant and comparable improvement in BCVA in anisometropic amblyopia up to 6 months of follow-up.